SEED SYSTEM OF GARLIC (ALLIUM SATIVUM L.) IN NORTH SHEWA ZONE, CENTRAL HIGHLANDS OF ETHIOPIA - BIZUAYEHU DESTA; KEBEDE WOLDETSADIK; WASSU MOHAMMED (Innovare Journal of Agricultural Sciences, 2024)
Objectives: The study aims to assess the status of both formal and informal garlic seed systems. In addition, it also investigates farmers’ indigenous knowledge related to seed selection, maintenance, seed sources, seed quality, and seed management practices in the North Shewa zone of the Amhara Regional State. Materials and Methods: The study employed a multistage sampling procedure. Accordingly, four districts and eight peasant associations (PAs) were purposively selected based on garlic production area; numbers of garlic grower, and representativeness of the farming system. The data were collected from randomly selected 160 garlic producer households (20 from each PAs) using structured questionnaires. Checklists were also used for key informants interview and focus group discussions. Results: In the study sites, the farmers’ cultivars/varieties were commonly grown. Farmers selected their seed based on different criteria. Bulb yield (90%), bulb size (85%), and early germination (83.8%) were the most dominant criteria. In all the study sites, informal seed source for all farmers was the initial seed source. Market seed was a predominant seed source; vast majority of farmers indicated that their initial seed source for garlic farming was obtained from market (95.6%). From 2013/14-2015/16: 61.2%, 51.2% and 62.5% of the farmers used seed from the market. The dissemination of improved varieties to farmers is still absent. The informal seed system should prioritize improving seed quality by increasing awareness and skills of farmers, improving seed quality of early generations, and market access. Conclusion: The provision of technical support and organizing farmers’ into cooperatives to handle the future production and distribution of seed and promoting the formal and informal seed sectors should be taken into account for sustainable supply of quality seed.